Peripheral Blood Flow Regulation in Human Obesity and Metabolic Syndrome - Limberg, Jacqueline K. (Exerc Sport Sci Rev, 2016)
Both obesity and metabolic syndrome are important cardiovascular disease risk factors. In this review, we will explore the hypothesis that young obese adults and adults with metabolic syndrome exhibit alterations in blood flow regulation that occur prior to the onset of overt cardiovascular dysfunction.